Sero-Diagnostic Concordance of Equine Infectious Anaemia in Saurashtra Region of Gujarat - Pandya, Meet K.; Mavadiya, Suresh V.; Padaliya, Nilesh R.; Vagh, Arshi A.; Bilwal, Avinash K.; Inamdar, Shruti H. (Indian Journal of Veterinary Sciences and Biotechnology, 2026)
Equine Infectious Anaemia (EIA) is a vector-borne retroviral disease of equids with significant implications for equine health, movement, and trade due to its lifelong persistence and lack of curative treatment. A sero-surveillance study was conducted in the Saurashtra region of Gujarat from January to June 2025, to generate baseline epidemiological data, assess the seroprevalence of Equine Infectious Anaemia Virus (EIAV), evaluate indirect ELISA (iELISA) in comparison with Agar Gel Immunodiffusion (AGID), and document associated clinicopathological alterations. A total of 514 horses of different age, sex, and breed were clinically examined and subjected to haematological, biochemical, and serological analyses. Based on suggestive clinical and clinicopathological findings, 47 horses (9.14%) were screened using RP-26-based iELISA, of which two (0.39%) were seropositive; however, none was confirmed by AGID, indicating an extremely low apparent EIAV prevalence. District-wise analysis showed that both seropositive horses originated from Bhavnagar district (2/117; 1.71%), with no positive cases in other districts of Saurashtra, resulting in an overall seroprevalence of 0.39% (2/514). Indirect ELISA showed high specificity (99.61%), overall accuracy (99.61%), and a negative predictive value of 100%.
Keywords: Agar Gel Immunodiffusion (AGID); Epidemiology; Equine Infectious Anaemia Virus (EIAV); Indirect ELISA (iELISA); Serosurveillance; Saurashtra region